Treatment of hypertension in patients with renal artery stenosis due to fibromuscular dysplasia of the renal arteries - Chrysant, Steven G. (AME Publishing Company, 2014)
Renal artery stenosis (RAS) from fibromuscular dysplasia (FMD) is an uncommon cause of hypertension that affects mostly women. FMD is a noninflammatory vascular disease that predominantly affects mainly the renal arteries, but can also affect arteries in other vascular territories. The most common type of FMD is the media fibroplasia with the characteristic “string of beads” appearance (80-90%), whereas the two other types, the “intimal” and “adventitial” FMD are much less common accounting for 10% and <5% of cases, respectively. The prevalence of FMD in the general population is not well known. Estimates are derived from screening kidney donors, with a prevalence of about 2.6%. Among patients with renovascular hypertension (RVH), its incidence is about 10%, whereas 80-90% of RVH is due to atherosclerotic renal artery stenosis (ARAS). The treatment of choice of hypertension due to FMD is percutaneous renal angioplasty (PTRA). In contrast, hypertension due to ARAS is not frequently responsive to PTRA. In order to achieve successful control of hypertension in patients with FMD, a combination of PTRA with drugs that block the renin-angiotensin-aldosterone system (RAAS) is often necessary. The purpose of this review was to search the literature for newer diagnostic methods and treatment of FMD. Therefore, a Medline search of the English literature of published papers between 2008 and December 2013 was performed. Of 58 papers reviewed, 19 pertinent papers were selected including, studies, reviews, registries and case reports. The information from these studies together with collateral literature will be discussed in this concise review.